2016
DOI: 10.1002/2015ja022214
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative GPS‐TEC ionospheric storm effects during the extreme space weather event of March 2015 over the Brazilian sector

Abstract: We studied the response of the ionosphere (F region) in the Brazilian sector during extreme space weather event of 17 March 2015 using a large network of 102 GPS‐ total electron content (TEC) stations. It is observed that the vertical total electron content (VTEC) was severely disturbed during the storm main and recovery phases. A wavelike oscillation with three peaks was observed in the TEC diurnal variation from equator to low latitudes during the storm main phase on 17–18 March 2015. The latitudinal extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 48 publications
10
114
0
Order By: Relevance
“…The main phase is characterized by two southward turning and one northward turning of IMF Bz (Figure ). These periods of the storm have clearly been identified by Borries et al () and reported in details in several other studies (e.g., Astafyeva et al, ; Fagundes et al, ; Kuai et al, ; Nava et al, ; Ramsingh et al, ; Venkatesh et al, ). Generally, when IMF Bz turns southward and there increase in PC potential, magnetospheric electric field penetrate promptly into the equatorial ionosphere (Kikuchi et al, ).…”
Section: Discussionsupporting
confidence: 73%
“…The main phase is characterized by two southward turning and one northward turning of IMF Bz (Figure ). These periods of the storm have clearly been identified by Borries et al () and reported in details in several other studies (e.g., Astafyeva et al, ; Fagundes et al, ; Kuai et al, ; Nava et al, ; Ramsingh et al, ; Venkatesh et al, ). Generally, when IMF Bz turns southward and there increase in PC potential, magnetospheric electric field penetrate promptly into the equatorial ionosphere (Kikuchi et al, ).…”
Section: Discussionsupporting
confidence: 73%
“…It is possible to infer that the composition changes would play an important role in this negative storm effect on 18 March over this region. Fagundes et al [] also found a strong positive phase under the action of an eastward PEF during the main phase of the March 2015 storm and a negative storm caused by [O]/[N 2 ] ratio changes during the recovery phase over the Brazilian sector, which are similar with the feature over the American sector.…”
Section: Resultsmentioning
confidence: 70%
“…The PPEFs due to sudden southward (northward) turnings of IMF Bz are eastward/westward (westward/eastward) on the daytime/nighttime sector and have lifetimes of tens of minutes to several hours (Huang, ; Tsurutani et al, , and the references therein). Regional‐scale ionospheric responses to the continuous PPEFs under steady and long‐duration southward IMF Bz have been widely investigated (e.g.Fagundes et al, , Li et al, , Mannucci et al, , Patra et al, ). By using GPS receiver data obtained during the “Halloween” storm of 29–30 October 2003, Mannucci et al () reported that the eastward PPEF results a significant strengthening and poleward expansion of the equatorial ionization anomaly (EIA), producing a “super‐fountain” effect with total electron content (TEC) enhancements up to 250% at low to middle latitudes in the Pacific sector.…”
Section: Introductionmentioning
confidence: 99%
“…Regional-scale ionospheric responses to the continuous PPEFs under steady and long-duration southward IMF Bz have been widely investigated (e.g. Fagundes et al, 2016, Li et al, 2010, Mannucci et al, 2005, Patra et al, 2016. By using GPS receiver data obtained during the "Halloween" storm of 29-30 October 2003, Mannucci et al (2005 reported that the eastward PPEF results a significant strengthening and poleward expansion of the equatorial ionization anomaly (EIA), producing a "super-fountain" effect with total electron content (TEC) enhancements up to 250% at low to middle latitudes in the Pacific sector.…”
Section: Introductionmentioning
confidence: 99%